2013
DOI: 10.1002/cncr.28411
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor activity and inactivation of galanin receptor type 2 by aberrant promoter methylation in head and neck cancer

Abstract: Frequent promoter hypermethylation in association with prognosis, and growth suppression after re-expression, supports the hypothesis that GALR2 may act to suppress tumor activity. GALR2 is a potentially significant therapeutic target and prognostic factor for this cancer type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 25 publications
0
38
0
3
Order By: Relevance
“…[16] Furthermore, the methylation of galanin significantly correlated with GALR1 and GALR2 methylation and reduced DFS. [4,5,15] The methylation of the gene pair of galanin and GALR1 in the primary tumor was associated with the most significant odds ratio of recurrence, [15] while another study concluded that GALR1 induces cell cycle arrest, and GALR2 induces both cell cycle arrest and apoptosis in HNSCC following galanin treatment. [24] this study shows that aberrant DNA methylation of SST and SSTR1 is not associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[16] Furthermore, the methylation of galanin significantly correlated with GALR1 and GALR2 methylation and reduced DFS. [4,5,15] The methylation of the gene pair of galanin and GALR1 in the primary tumor was associated with the most significant odds ratio of recurrence, [15] while another study concluded that GALR1 induces cell cycle arrest, and GALR2 induces both cell cycle arrest and apoptosis in HNSCC following galanin treatment. [24] this study shows that aberrant DNA methylation of SST and SSTR1 is not associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[18] UM-SCC cell lines were kindly provided by Dr. Thomas E. Carey of the University of Michigan and were validated by genotyping in his laboratory. [4,5]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Орексин-А стимулирует аутофагию опухолевых клеток (линия HCT-116, карцинома прямой кишки) за счет мо-дуляции сигнального пути ERK, поддерживающего ба-ланс между выживанием и апоптозом клеток [16]. Низкая активность рецепторов галанина (например при избыточ-ном метилировании участков ДНК, кодирующих гены этих рецепторов) стимулирует рост опухолей головы и шеи [17,18].…”
unclassified